Comprehensive Technique for Jute Fibre Retting - Sarkar, S.; Sengupta, K. (International Journal of Bio-resource and Stress Management, 2023)
Jute is one of the important cash crops of in the South East Asian countries like India, Bangladesh etc. The extraction of mature jute fibre by natural microbial process known as retting. The microbes involves in retting process consume the non-fibrous cementing materials like pectin and hemicellulose. Both over and under retting reduce the fibre quality. The main problem of Jute cultivation of these areas is the retting problem due to unavailability of sufficient amount good quality of free flowing mild water during the harvesting time of the Jute due to irregularity of Monsoon rain i.e. May-June. In conventional retting process, decomposition of whole jute plant in stagnant water, so retting causes environmental pollution as well as reducing the quality of fibre. In ribbon retting, ribbons are stripped out mechanically from the stem of mature jute plants, coiled and allowed to ret under water. Ribbon retting reduces time of normal retting by 4 to 5 days. Moreover, requirement of water for ribbon retting is almost half in comparison to conventional whole plant retting under normal condition. This also reduces environmental pollution to a great extent. But use of efficient pectinolytic microbial consortium improves quality of fibre, further reduce the time of retting and the environmental pollution. There for the present study indicates the appropriate method of retting method to enhance the quality of the Jute fibre in terms of fibre strength, colour and txture for the thousands of jute growers South East Asian Countries based on the available technological resources